2010
DOI: 10.7863/jum.2010.29.11.1555
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Assessment of the Nasal Bones Using the Retronasal Triangle View

Abstract: Objective. The purpose of this study was to evaluate a new sonographic technique for identifying the nasal bones using the retronasal triangle view, ie, the coronal plane at which the palate and frontal processes of the maxilla are simultaneously visualized. Methods. Three-dimensional (3D) volumes were acquired from women undergoing first-trimester sonographic screening for aneuploidy by 2 accredited operators. Those data sets in which the fetal face was clearly identified were selected for offline analysis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Unilateral nasal bone often presents as absent nasal bone in midsagittal view [19]. This differentiation can easily be found in RNT view; where the nasal bones appear as two echogenic dots at the apex of triangle [15,19]. In the present series authors had three cases where the nasal bone was absent in the first trimester but appeared normal in the second trimester and hence the obtained FTS risk was not modified in these three cases.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Unilateral nasal bone often presents as absent nasal bone in midsagittal view [19]. This differentiation can easily be found in RNT view; where the nasal bones appear as two echogenic dots at the apex of triangle [15,19]. In the present series authors had three cases where the nasal bone was absent in the first trimester but appeared normal in the second trimester and hence the obtained FTS risk was not modified in these three cases.…”
Section: Discussionmentioning
confidence: 56%
“…The ossification pattern of nasal bone may be the presence of only one nasal bone or hypoplastic nasal bones or complete absence of nasal bone. Unilateral nasal bone often presents as absent nasal bone in midsagittal view [19]. This differentiation can easily be found in RNT view; where the nasal bones appear as two echogenic dots at the apex of triangle [15,19].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the detection rate for any fetal structural malformation in the first trimester only reaches a value in the range 0.7−4.7% [24]. Reports of CP in the first trimester are scarce [10,][11,26,27,28]. Syngelaki et al [25] demonstrated a 5% detection rate for facial cleft with non-chromosomal abnormalities at 11-13 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the RNT may become an important sonographic landmark for several fetal anomalies as understanding and technology improves. Martinez-Ten et al [28] found the nasal bones could be confidently identified in the coronal plane as paired echogenic structures located at the upper tip of the RNT, which might be advantageous over a midsagittal assessment, in which only 1 of the 2 nasal bones can be evaluated. Sepulveda et al [31] found the disappearance of the space between the left and right mandibular bodies in the RNT and this finding may help to diagnose micrognathia deformity in the first-trimester.…”
Section: Discussionmentioning
confidence: 99%
“…98 The retronasal triangle can be used to identify the paired nasal bones, premaxillary processes, primary palate, and the mandible. [99][100][101][102] The absence of the mandibular gap raises a concern for micrognathia. 101 A sweep of the coronal planes can be used to demonstrate the orbits, lenses, and integrity of the upper lip.…”
Section: Fetal Face and Profilementioning
confidence: 99%